Relationship Between Corporate Governance and Corporate Social Responsibility: Evidence From Nepalese Commercial Banks - Poudel, Resam Lal (Journal of Nepalese Business Studies, 2016)
The research paper aims to show the relationship between corporate governance (CG) and corporate social responsibility (CSR) disclosure in Nepalese commercial banks. In simple terms corporate governance is the system by which companies are governed. It is a set of rules and behaviors according to which companies are managed and controlled. Corporate social responsibility or sustainability is an important feature in contemporary business addresses different aspects like business ethics, stakeholder’s management and social performance. Effective corporate governance is expected to support effective and efficient corporate social responsibility within commercial banks. The content analysis of 10 commercial banks composing 5 Joint Venture (JV) Banks and 5 Non Joint Venture (NJV) Banks though judgmental sampling method based on stratified sampling technique was used to extract CSR disclosure items and corporate governance factors from secondary data specifically annual report for the period of one year. T-test was employed to test the level of significance. Regression analysis was used to examine the relationship between corporate social responsibility disclosure and independent variables associated with corporate governance practices. The study reveals that different variables associated with corporate governance practices are positively and significantly correlated with the level of corporate social responsibility initiatives based on all three models. The paper is useful to organization and statutory bodies to take consideration of corporate governance practices which will enhance corporate social responsibility initiatives. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp.137-144